Evaluation of Single Tooth Dental Implants Ten Years Survival Rate. A Clinical and Radiolographic study - S , Santhosh; P.K, Sasikumar; R, Dhivya; S, Visalini; M, Radhika; Angel J, Jasmine (Journal of Neonatal Surgery, 2025)
Aim: The aim of the study is to compare early loaded versus delayed loaded implants after ten years of placement. Materials and Methods: Among 14 patients who underwent implant placement three patients from delayed loaded category and three patients from early loaded category were available for evaluation of dental implants after ten years. The parameters like plaque index, gingival index, thickness of peri-implant mucosa, probing pocket depth and radiographic bone loss was measured around the dental implants. These readings were compared with baseline and after ten years in both delayed loaded implants and early loaded implants. Results: In both early loaded category and delayed loaded category the parameters like plaque index, gingival index, implant mobility and radiographic bone loss increased from baseline to 10 years but was not significant. Thickness of peri- implant mucosa increased in early loaded category only. Probing pocket depth increased significantly in both early and delayed loaded category. Conclusion: The study showed that both delayed loaded implants and early loaded implants did not show any significant difference in their durability and function even after 10 years of implant placement.